2021
DOI: 10.3390/su13115931
|View full text |Cite
|
Sign up to set email alerts
|

Investigating the Impact of Regional Temperature on COVID-19 Pandemic during 2020

Abstract: Several studies have attempted to uncover the impact of weather parameters on the coronavirus (COVID-19) pandemic during the initial stage of its outbreak. However, they reported contradicting findings due to limited data available at an earlier stage of the outbreak. Therefore, in this study, we investigate the impact of regional temperature on the pandemic in 34 different locations of the globe by defining two main objectives. The first objective is focused on pattern analysis of an earlier stage of the pand… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
4
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(4 citation statements)
references
References 20 publications
0
4
0
Order By: Relevance
“…Studies show that the COVID-19 closure has decreased surface temperatures. Our work evaluated LST variations, just like earlier studies (Arrofiqoh & Setyaningrum, 2021 ; Ghosh et al, 2020 ; Marvi et al, 2021 ; Taoufik et al, 2021 ; Teufel et al, 2021 ) that noted urban temperature changes as a result of COVID-19. We used 14 LANDSAT 8 OLI/TIRS satellite images from 2016 and 2022 to calculate the LST values.…”
Section: Discussionmentioning
confidence: 99%
“…Studies show that the COVID-19 closure has decreased surface temperatures. Our work evaluated LST variations, just like earlier studies (Arrofiqoh & Setyaningrum, 2021 ; Ghosh et al, 2020 ; Marvi et al, 2021 ; Taoufik et al, 2021 ; Teufel et al, 2021 ) that noted urban temperature changes as a result of COVID-19. We used 14 LANDSAT 8 OLI/TIRS satellite images from 2016 and 2022 to calculate the LST values.…”
Section: Discussionmentioning
confidence: 99%
“…Secondly, it was learned through a literature review that the activity of indirect transmission of coronaviruses on the surface of objects diminishes with time, and that this change in the possibility of decline depends on the influence of surrounding environmental factors [ 32 ]. After the investigation of express box transportation, it was found that the main transport environment of express boxes is closed, and the factors that can have an impact on virus transmission in express box transportation are the following: (1) Disinfection, the preventive measures for the express field after the epidemic are mainly the disinfection of the transport environment before shipment, and disinfection is currently the key link to contain and interrupt the spread of COVID-19 [ 33 ]; (2) The volume of the carriage in express box transport, which is a constraint affecting the range of virus transmission and the volume of express box transport; (3) Temperature, which can directly affect the active degree of the virus in express transport, which plays an important role in virus transmission [ 1 , 2 , 3 , 4 , 5 , 6 , 7 ]; (4) Virus release intensity, the intensity of free transmission of the virus itself without interference, correlation with the basic regeneration number of virus transmission, which will directly determine the intensity of transmission of different viruses in the initial stage [ 31 ]; (5) Humidity, where lower humidity increases the persistence of coronaviruses [ 7 , 8 ]. Additionally, it has been demonstrated that relative humidity is negatively correlated with the global spread of COVID-19, with a 0.19% decrease in the percentage of new cases for every 1 percentage point increase in relative humidity [ 34 ].…”
Section: Method: Express Box Dynamic Modelmentioning
confidence: 99%
“…A research team from the University of Hong Kong found that coronaviruses can survive for more than 4 days in culture media and that the viruses are highly stable at 5 °C [ 2 ]. Other scholars studying the spread of the COVID-19 virus in different temperatures, humidity, and closed or open environments found that cold and dry conditions were enhancers of virus spread, and these factors were further enhanced in closed environments [ 3 , 4 , 5 , 6 , 7 , 8 ]. Coronaviruses and infectious diseases with similar transmission characteristics require some pathway to cause spatial spread on a global scale.…”
Section: Introductionmentioning
confidence: 99%
“…Despite the reported associations found between climate factors and COVID-19 cases, most studies to date have included less than five months of data in their analysis or have only reported on one country [16][17][18][19]. A more recent study found a significant relationship between average temperature and the number of new cases in Bahrain and Qatar, two countries in the GCC, over a three month and subsequent 12 month period [20]. However, further trend analyses are required over a longer time period in order to establish the true impact of climate changes on COVID-19 cases, especially for GCC countries, where such studies are lacking.…”
Section: Introductionmentioning
confidence: 99%